Lymphedema : presentation, diagnosis, and treatment - Greene, Arin K.; Slavin, Sumner A.; Brorson, Håkan (Springer, 2015)
This volume is a clinically-oriented book that can be used for patient care, teaching, or research. It covers the entire field of lymphedema, including both primary and secondary disease, as well as all diagnostic and treatment modalities. The text begins with a foundation for the condition, including its pathophysiology, epidemiology, and morbidity. Next, the classification of lymphedema is covered which is the template for accurate diagnosis. Clinical, radiological, and differential diagnosis of lymphedema is also reviewed. Finally, conservative and operative management is presented, including both physiologic and excisional procedures. Lymphedema: Presentation, Diagnosis, and Treatment provides a comprehensive, easy-to-read reference for any health care provider managing a patient with lymphedema. The text is clinically-focused, evidence-based, and practical. The reader, regardless of his/her level of training or specialty, will be able to adequately treat a patient with lymphedema using this resource. To facilitate its use in clinical settings, the book was designed to be portable. In addition, diagnostic and treatment algorithms are included to further simplify the management of these patients. Patient images are presented throughout the text to illustrate the clinical care of lymphedema. All chapters are written by experts in the field, and contain the most current information on the topic.